2015
DOI: 10.1021/acsami.5b06606
|View full text |Cite
|
Sign up to set email alerts
|

On the Control of the Fixed Charge Densities in Al2O3-Based Silicon Surface Passivation Schemes

Abstract: A controlled field-effect passivation by a well-defined density of fixed charges is crucial for modern solar cell surface passivation schemes. Al2O3 nanolayers grown by atomic layer deposition contain negative fixed charges. Electrical measurements on slant-etched layers reveal that these charges are located within a 1 nm distance to the interface with the Si substrate. When inserting additional interface layers, the fixed charge density can be continuously adjusted from 3.5 × 10(12) cm(-2) (negative polarity)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
95
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 117 publications
(107 citation statements)
references
References 60 publications
(126 reference statements)
10
95
1
Order By: Relevance
“…It was noted that in the Al 2 O 3 sample, the D it had decreased from 1.0 × 10 12 cm −2 eV −1 to 5.5 × 10 10 cm −2 eV −1 and Q f had increased from −3.5 × 10 12 cm −2 to 1.4 × 10 13 cm −2 after 400 W plasma nitridation. This clearly corroborates the formation of decreased interface defects and negative fixed charges [16,17].…”
Section: Resultssupporting
confidence: 77%
“…It was noted that in the Al 2 O 3 sample, the D it had decreased from 1.0 × 10 12 cm −2 eV −1 to 5.5 × 10 10 cm −2 eV −1 and Q f had increased from −3.5 × 10 12 cm −2 to 1.4 × 10 13 cm −2 after 400 W plasma nitridation. This clearly corroborates the formation of decreased interface defects and negative fixed charges [16,17].…”
Section: Resultssupporting
confidence: 77%
“…It might be due to nonstoichiometric initial growth (increased O/Al ratio has been found within the first several Al 2 O 3 monolayers on Si) leading to formation of negatively charged defects (interstitial oxygen and Al vacancies). Simon, et al have suggested that the negative charge results from the tetrahedrally coordinated Al which is dominant at the interface. The present investigation reveals that negative charge is observed after high temperature treatment which implies that they are formed as a result of some intermixing at HfO 2 /Al 2 O 3 interface and breaking of bonds.…”
Section: Resultsmentioning
confidence: 99%
“…The N F was quantified experimentally in MOSCAP structures by measuring the capacitance‐voltage ( C–V ) characteristics and relating V fb to fixed charge according to Equations and qVfb=normalΦMSEOTtrue[NFϵ0ϵnormalSnormalinormalOnormalxtrue]normalEnormalOnormalT2qρhighk2ϵ0ϵSiOxnormalΦDipole NfF=Coxqtrue(ΦnormalMnormalSqVnormalfnormalbtrue) …”
Section: Resultsmentioning
confidence: 99%